Recombinant Ricin Toxin Binding Subunit B (RTB) Stimulates Production of TNF-α by Mouse Macrophages Through Activation of TLR4 Signaling Pathway - Xu, Na; Yu, Kaikai; Yu, Haotian; Zhang, Jianxu; Yang, Yang; Dong, Mingxin; Wang, Yan; Chang, Ying; Sun, Yucheng; Hou, Yanguang; Sun, Chengbiao; Wan, Jiayu; et al. (Frontiers in Pharmacology, 2020)
Ricin toxin binding subunit B (RTB) is a galactose-binding lectin protein derived from the beans of the castor oil plant (Ricinus communis). Our previous studies have reported a direct immunomodulatory effect of recombinant RTB, which stimulates RAW264.7 cells to produce cytokines including TNF-α. However, the effect of RTB on the innate immune response and its mechanism are not well characterized. In the present study, the results showed that RTB treatment of macrophages significantly increased TLR4 protein levels. RTB also activated TLR4 downstream events, including MyD88, IRAK, and TRAF6, resulting in macrophage activation and TNF-α production. This process was accompanied by an increase in phosphorylation of IκB. TLR4 knockdown macrophages treated with RTB exhibited greatly reduced IκB phosphorylation and TNF-α secretion. Moreover, treatment with MyD88 inhibitor also suppressed TNF-α production. A computerized simulation indicated that RTB formed a contacted interface with TLR4. Our results suggest that recombinant RTB can activate mouse macrophages to secrete TNF-α through activation of NF-κB via the TLR4 signaling pathways.